High frequency of temperature-sensitive mutants of p53 in glioblastoma - Smardova, Jana; Liskova, Kvetoslava; Ravcukova, Barbora; Kubiczkova, Lenka; Sevcikova, Sabina; Michalek, Jaroslav; Svitakova, Miluse; Vybihal, Vaclav; Kren, Leos; Smarda, Jan (Pathology oncology research, 2013)
Glioblastoma is the most common and the most aggressive type of brain cancer. Aberrations of the RTK/RAS/PI3K-, p53-, and RB cell signaling pathways were recognized as a core requirement for pathogenesis of glioblastoma. The p53 tumor suppressor functions as a transcription factor transactivating expression of its target genes in response to various stress stimuli. We determined the p53 status in 36 samples of glioblastoma by functional analyses FASAY and split assay. Seventeen p53 mutations were detected and further analyzed by cDNA and gDNA sequencing in 17 patients (47.2 %). Fifteen (88.2 %) of the mutations were missense mutations causing amino acid substitutions, seven of them exhibited temperature-sensitivity. Two mutations were determined as short deletions, one of them causing formation of premature termination codon in position 247. Fluorescent in situ hybridization revealed the loss of the p53-specific 17p13.3 locus in four of 33 analyzed samples (12 %). In 12 out of 30 samples (40 %), the p53 protein accumulation was shown by immunoblotting. There was high (80 %) concordance between the presence of the clonal p53 mutation and the p53 protein accumulation.
Keywords: mutace; Tumor Suppressor Protein p53; orgánová specificita; Female; Genes, p53; Cell Line, Tumor; teplota; ženské pohlaví; delece genu; mutační analýza DNA; nádory mozku; geny p53; lidé; Yeasts; DNA Mutational Analysis; Mutation; glioblastom; Glioblastoma; Temperature; Gene Deletion; Male; kvasinky; Aged; nádorový supresorový protein p53; Brain Neoplasms; Sequence Analysis, DNA; Organ Specificity; hybridizace in situ fluorescenční; lidé středního věku; senioři; mužské pohlaví; sekvenční analýza DNA; In Situ Hybridization, Fluorescence; Middle Aged; nádorové buněčné linie; Humans